2005
DOI: 10.1063/1.2043252
|View full text |Cite
|
Sign up to set email alerts
|

Charge trapping and detrapping characteristics in hafnium silicate gate dielectric using an inversion pulse measurement technique

Abstract: Articles you may be interested inCharge trapping induced drain-induced-barrier-lowering in HfO2/TiN p-channel metal-oxide-semiconductor-fieldeffect-transistors under hot carrier stress Appl. Phys. Lett. 100, 152102 (2012); 10.1063/1.3697644Structural, electronic, and dielectric properties of amorphous hafnium silicates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…In particular, the formation of a low dielectric-constant hafnium silicate interfacial layer 9 and the presence of oxygen defects at both the hafnia/silicon interface and in the hafnia film that trap electrons lead to a decrease in channel mobility and an instability in the threshold voltage. 10,11 Hafnia crystallizes into three crystalline polymorphs at ambient pressure: a monoclinic ͑P2 1 / c͒ phase, a tetragonal ͑P4 2 nmc͒ phase, and a cubic fluorite ͑Fm3m͒ phase. The monoclinic-to-tetragonal transition takes place at 2000 K while the tetragonal-to-cubic transition occurs at 2900 K. The melting point of the cubic phase is at 3085 K. 12 There are also two high-pressure phases: the orthorhombic I phase ͑Pbca, Brookite-type structure͒ above 10 GPa and the orthorhombic II phase ͑Pnma, PbCl 2 -type, or cotunnite structure͒ above 30 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the formation of a low dielectric-constant hafnium silicate interfacial layer 9 and the presence of oxygen defects at both the hafnia/silicon interface and in the hafnia film that trap electrons lead to a decrease in channel mobility and an instability in the threshold voltage. 10,11 Hafnia crystallizes into three crystalline polymorphs at ambient pressure: a monoclinic ͑P2 1 / c͒ phase, a tetragonal ͑P4 2 nmc͒ phase, and a cubic fluorite ͑Fm3m͒ phase. The monoclinic-to-tetragonal transition takes place at 2000 K while the tetragonal-to-cubic transition occurs at 2900 K. The melting point of the cubic phase is at 3085 K. 12 There are also two high-pressure phases: the orthorhombic I phase ͑Pbca, Brookite-type structure͒ above 10 GPa and the orthorhombic II phase ͑Pnma, PbCl 2 -type, or cotunnite structure͒ above 30 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown that, in addition to FTC, high-κ gate dielectrics also demonstrate fast relaxation of the trapped charge, although on a slightly longer time scale [88,104]. Fig.…”
Section: Fast Transient Trapped Charge Relaxationmentioning
confidence: 99%
“…Defects at the interface and in the bulk oxide trap charge reduce channel mobility ͑deep traps͒, increase leakage current ͑shallow traps͒, 2,7-9 and causing instability of the threshold voltage. 10 In standard MOSFET fabrication, defects in SiO 2 are passivated by hydrogen, but in HfO 2 this causes as many problems as it solves. 11 Various other postdeposition treatments have been tried, especially nitrogen-based, 12 but with little success in reducing fixed charge in the insulator.…”
Section: Introductionmentioning
confidence: 99%